Morfológia l'udského rebrového perichondria z hl'adiska artroplastiky drobných kl'bov ruky - Brozman, M; Jakubovský, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 1989)
The human rib perichondrium is a suitable material for reconstruction interventions on small joints of the hand. Optical and electron microscopy analysis of the human rib perichondrium has shown some features different from the similar perichondrium in rabbits. In its superficial layers there are apart from the vascularity also myelinized nerve fibres, fat-cells and heparinocytes. In the medium layer and in the inner layer of the perichondrium there are cells which by their characteristics correspond to fibrocytes. Among them are collagen fibrillae coated with materials which can be fixed by the ruthenium red. The inner layer cannot be exactly distinguished from the cartilage of the rib.
Keywords: chrupavka; artroplastika; Arthroplasty; Ribs; ruka; buňky pojivové tkáně; Humans; lidé; žebra; Hand; Cartilage; Connective Tissue Cells